THE INFLUENCE OF INCOME ON EMPLOYEE MOTIVATION - Daffin Mandala Putra; Muammar Khaddafi; Febro Febrian Pratama; Syukror Rozi; Donny Hartanto; Trio Ardhimansyah; Andy Achmad (Universitas Efarina, 2023)
This comprehensive analysis explores the interplay between income, employee motivation, and compensation strategies, drawing insights from various studies in education and industry. The research, conducted using quantitative methods, uncovers a robust positive correlation between income and work motivation, highlighting the pivotal role of financial rewards in reinforcing desired work-related behaviors. Employing statistical analyses, the study quantifies the impact of income on motivation, providing empirical evidence of its significance. Nonetheless, it underscores the importance of adopting a holistic compensation approach that encompasses both extrinsic and intrinsic motivators. Organizations are advised to implement transparent and equitable compensation systems, offer performance-related incentives, and facilitate avenues for career growth. Moreover, cultivating a positive work environment characterized by open communication and recognition of employee contributions is emphasized as a key driver of job satisfaction and sustained motivation.